Induced genetic ablation of Rest leads to the alteration of stimulus‐induced response of the vagal nerve. (13th January 2021) - Aoki, Hitomi; Abe, Chikara; Hara, Akira; Miyazaki, Tatsuhiko; Morita, Hironobu; Kunisada, Takahiro
Abstract: Rest (RE1‐silencing transcription factor, also called Nrsf) is involved in the maintenance of the undifferentiated state of neuronal stem/progenitor cells by preventing precocious expression of neuronal genes. In order to further investigate the function of Rest in neurons, we generated and examined mice evoking genetic ablation of Rest specifically in neural tissues by generating Rest conditional knockout mice. As the Rest knockout mice are embryonically lethal, we used a Sox1‐Cre allele to excise the floxed Rest gene from the early stage of nerve cell differentiation including neural crest‐derived nerve cells. Using this conditional Rest knockout Sox1‐Cre; Rest flox/flox mice, we have revealed the role of Rest in the parasympathetic nervous system in the stomach and heart Abstract : Rest is involved in the maintenance of the undifferentiated state of neuronal stem/progenitor cells by preventing precocious expression of neuronal genes. To investigate the function of Rest in neurons, we generated mice evoking genetic ablation of Rest specifically in neural tissues by generating Rest conditional knockout mice. Using these conditional Rest knockout mice, we have revealed the role of Rest in the parasympathetic nervous system in the stomach and heart.